DISSENTING OPINION PUTUSAN SENGKETA MEREK PIERRE CARDIN INDONESIA MELAWAN PIERRE CARDIN PERANCIS DALAM KAJIAN HUKUM ISLAM: Studi Putusan Mahkamah Agung Nomor 557 K/Pdt.Sus-HKI/2015 - Mahmudah, Masrifatun (Fakultas Syariah, 2017)
This article intents to examine the dissenting opinion in the judges consideration on the Supreme Court Decision No. 557 K/Pdt.Sus-HKI/2015. This article is normative research with statute approach dan conceptual approach. The legal material on this research consist of primery legal materials namely Law No. 15 of 2001 on Trademark and Supreme Court Decision No. 557 K/Pdt.Sus-HKI/2015, while the secondary legal materials are books, journals, research related to trademarks. The judge decide to reject the application of Pierre Cardin because the petition of Pierre Cardin has passed a period of five years from the registration of Pierre Cardin Indonesia. However, the conclusion of this study revealed that Pierre Cardin entitled to be protected because it is a well-known mark. Finally, Pierre Cardin Indonesia has violeted the terms of article 4 jo article 6 paragraph (1) letter b of Trademark Law because he has a bad faith and had imitated the well-known mark.